2023
DOI: 10.3390/w15050964
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Features of River Runoff and Their Effect on the State of the Aquatic Environment of Lake Onego

Abstract: This paper presents the results of seasonal observations of the geochemical composition of the waters of the large tributaries of Lake Onego. The mineralogy and geochemistry of the suspended matter and the isotopic composition (oxygen-18 and deuterium) of the river waters were studied for the first time. The dependence of the chemical and isotopic compositions of the tributary water on the season and characteristics of the catchment area (swampiness and lacustrine) was revealed. It is shown that the river wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Since 2009, the Northern Water Problems Institute (NWPI) at the Karelian Research Centre of RAS and Saint Petersburg State University (SPbSU) has been studying the water dynamics in the lake and the conditions of water-balance formation on the watershed by using stable isotope tracers (deuterium and oxygen-18) to better understand the processes responsible for Lake Onega's conditions. Measurements in 2012-2017 in the Petrozavodsk Bay and its three tributaries and in the central part of Lake Onega showed that the snowmelt floods had the greatest effect on the water dynamics in the bay while evaporation had the greatest effect in the open lake [27,28]. Precipitation, tributaries and groundwater were sampled, and the impact of evaporation on the deuterium and oxygen-18 concentrations in the residual water was experimentally tested.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, the Northern Water Problems Institute (NWPI) at the Karelian Research Centre of RAS and Saint Petersburg State University (SPbSU) has been studying the water dynamics in the lake and the conditions of water-balance formation on the watershed by using stable isotope tracers (deuterium and oxygen-18) to better understand the processes responsible for Lake Onega's conditions. Measurements in 2012-2017 in the Petrozavodsk Bay and its three tributaries and in the central part of Lake Onega showed that the snowmelt floods had the greatest effect on the water dynamics in the bay while evaporation had the greatest effect in the open lake [27,28]. Precipitation, tributaries and groundwater were sampled, and the impact of evaporation on the deuterium and oxygen-18 concentrations in the residual water was experimentally tested.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is vital in the water cycle [24][25][26][27]. Affected by air masses that bring water vapor from different geographical regions, hydrogen and oxygen isotopes in precipitation reflect a combination of precipitation and recycling effects in the source area, providing the possibility of determining precipitation sources and quantifying the contribution of precipitation sources to runoff generation [28,29], as well as the dynamic processes of the watershed (such as evaporation, mixing of different sources) [30]. Numerous studies have shown that the distribution of precipitation isotopes depends on local temperature, latitude, altitude, and other climatic or geographical factors, which can be summarized as the following effects: seasonal, precipitation, temperature, continental, latitude, and sea level effects [11,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%